Takhrij and Syarah Hadith of Agrotechnology Benefits of Habbatus Sauda - Sarah Salsabila; Wahyudin Darmalaksana; Cecep Hidayat (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadiths of the benefits of Habbatus Sauda or Jinten Hitam as one of the gifts Allah bestows upon humans. The research method used in the processing of takhrij and sharah hadith is a qualitative method. The results and discussion of this study is that Habbatus Sauda or Jinten Hitam has many benefits for the body and is also useful as a medicine for a number of acute diseases. The conclusion of this study is that Black Seed can be a cure for a number of acute diseases in accordance with the hadith of the Prophet Muhammad.